TBI-CareQOL military health care frustration in caregivers of service members/veterans with traumatic brain injury. - Carlozzi, Noelle E.; Lange, Rael T.; French, Louis M.; Kallen, Michael A.; Boileau, Nicholas R.; Hanks, Robin A.; Nakase-Richardson, Risa; Massengale, Jill P.; Sander, Angelle M.; Hahn, Elizabeth A.; Miner, Jennifer A.; Brickell, Tracey A. (Rehabilitation Psychology, 2020)
Purpose: Caregivers of service members/veterans (SMVs) encounter a number of barriers when navigating the military health care system. The purpose of this study was to develop a new measure to assess potential caregiver frustration with the systems of care and benefits in the United States Departments of Defense and Veterans Affairs. Method: The TBI-CareQOL Military Health Care Frustration measure was developed using data from 317 caregivers of SMVs with TBI who completed an item pool comprised of 64 questions pertaining to anger or frustration with accessing military health care services. Results: Exploratory and confirmatory factor analyses supported the retention of 58 items. Constrained graded response model (GRM) overall fit and item fit analyses and differential item functioning investigations of age and education factors supported the retention of 43 items in the final measure. Expert review and GRM item calibration products were used to inform the selection of two 6-item static short forms (TBI-CareQOL Military Health Care Frustration-Self; TBI-CareQOL Military Health Care Frustration-Person with TBI) and to program the TBI-CareQOL Military Health Care Frustration computer adaptive test (CAT). Preliminary data supported the reliability (i.e., internal consistency and test-retest reliability) as well as the validity (i.e., convergent, discriminant, and known-groups) of the new measure. Conclusions: The new TBI-CareQOL Military Health Care Frustration measure can be used to examine caregiver perceptions of and experience with the military health care system, to target improvements.